Serum collectrin levels in patients with early- and late-onset preeclampsia. (2nd November 2018) - Aslan Cetin, Berna; Aydogan Mathyk, Begum; Cift, Tayfur; Tuten, Abdullah; Bulut, Berk; Yilmaz, Nevin; Erenel, Hakan; Ekmekci, Hakan; Gezer, Altay
Abstract: Aim: The aim of this study is to investigate the maternal levels of collectrin in early-onset preeclampsia (EOPE) and late-onset preeclampsia (LOPE). To assess the correlation between serum collectrin levels and blood pressure in humans. Material and methods: This cross-sectional study was conducted including 79 pregnant women, 27 with normal pregnancy, 30 with EOPE and 22 with LOPE. Maternal serum levels of collectrin were measured by using enzyme-linked immunosorbent assay kits. Results: The mean serum collectrin level was significantly lower in women with PE compared with the control group (8.49 ± 3.12 ng/ml (EOPE), 9.69 ± 3.01 ng/ml (LOPE) versus 11.51 ± 4.33 ng/ml) and was found to be the lowest in the EOPE group (8.49 ± 3.12 ng/ml). The mean serum urea and uric acid levels were significantly higher in the PE group than the control group. Serum collectrin concentrations did not correlate with maternal age, BMI and serum creatinine levels. However, collectrin concentrations were negatively correlated with systolic blood pressure ( r  = −0.284, p  = .011) and diastolic blood pressure ( r  = −0.275, p  = .014) as well as with maternal serum urea ( r  = −0.269, p  = .017) and uric acid ( r  = −0.219, p  = .049) concentrations. Conclusion: Maternal serum collectrin levels are significantly lower in patients with preeclampsia than in the control group. There is an inverse correlation between serum collectrin levels and blood pressure.